2008
DOI: 10.1177/0734282908319664
|View full text |Cite
|
Sign up to set email alerts
|

Development and Measurement Through Confirmatory Factor Analysis of the Young Adult Social Behavior Scale (YASB)

Abstract: The Young Adult Social Behavior Scale was developed for the purpose of measuring selfreported relational and social aggression and behaviors of interpersonal maturity in adolescents and young adults (the sample included 629 university students; 66% female; 91.6% White). Despite previous research suggesting that relational and social aggression comprise a single paradigm, there is emerging evidence that indirect, social, and relational aggression are, in fact, separate constructs. In accordance with this more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 29 publications
0
46
1
1
Order By: Relevance
“…The YASB is composed of 14 statements rated on a scale from 1 (never) to 5 (always) pertaining to participants' use of aggression in social situations. The authors did not report internal consistency or test-retest reliability for this scale (Crothers et al, 2009). However, the current research found the YASB to have a Cronbach's alpha of .79.…”
Section: Psi Chi Journal Of Psychological Researchcontrasting
confidence: 70%
See 1 more Smart Citation
“…The YASB is composed of 14 statements rated on a scale from 1 (never) to 5 (always) pertaining to participants' use of aggression in social situations. The authors did not report internal consistency or test-retest reliability for this scale (Crothers et al, 2009). However, the current research found the YASB to have a Cronbach's alpha of .79.…”
Section: Psi Chi Journal Of Psychological Researchcontrasting
confidence: 70%
“…Young adults have been found to engage in socially aggressive behaviors like any other age group, and several studies have confirmed the presence of cyberbullying within this population (Crothers, Schreiber, Field, & Kolbert, 2009;Kowalski et al, 2014;Roland, 2013;Schenk & Fremouw, 2012). Even so, there continues to be a noticeable gap in cyberbullying research, specifically relating to the young adult population.…”
Section: Current Studymentioning
confidence: 93%
“…Archer and Coyne [29] describe three different terms -indirect aggression, relational aggression, and social aggression -that some researchers have considered distinct behaviors, while others believe that the terms are synonymous. Recent evidence has suggested, however, that relational and social aggression are separate and distinct constructs and this paper will adopt that conclusion [30,31].…”
Section: Types Of Bullying Behaviorsmentioning
confidence: 93%
“…As a result, indirect forms of aggression become more common. What is more, girls' earlier maturation in the area of social and verbal skills allows them to make use of indirect forms of aggression earlier than boys (Crothers et al, 2009). …”
Section: Socially Oriented Aggression and Gendermentioning
confidence: 96%
“…However, other forms of aggression that receive lesser attention appear to be widespread and of critical importance. Socially oriented aggression, sometimes defined as relational aggression or indirect aggression (Björkqvist et al, 2001), involves either covert or overt actions that victimize another person (Crothers, Schreiber, Field, & Kolbert, 2009;Gomes, 2007;Leenars & Rinaldi, 2010). These acts could include a range of behaviors such as gossiping, social isolation, spreading rumors, composing and delivering hurtful messages, or cold glances directed at peers.…”
mentioning
confidence: 98%